Novel photosensitive collagen bio-ink for 3D printing as well as preparation method and application of novel photosensitive collagen bio-ink

Modify collagen through mainalide, prepare the aluminyl collagen (CIA) with high solubility and enhance biological activity, and prepare a new type of optical collagen biological ink for 3D printed in combination with other ingredients. It solves the problem of insufficient solubility and limited mechanical properties under neutral conditions, and achieves efficient 3D printing and diabetic wound healing effects.

CN119367608APending Publication Date: 2025-01-28COLLAGEN (WUHAN) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410905663.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-08
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The inadequate solubility of collagen under neutral conditions limits its application in 3D printing and may cause potential irritation and damage to cells and tissues. Existing photosensitive collagen bioinks have problems with insufficient solubility and limited mechanical properties, resulting in poor printing quality and efficiency.

Method used

Modify collagen through isanide, and prepare coebarized collagen (CIA). This material has a significant reduction of electrical points and contact angles to introduce more hydrophilic groups to improve solubility. Combined with phenyl-2,4,6-lithium-based lithium-based lithium-based and ultraviolet absorbers to prepare a new type of optical collagen biological ink for 3D printed.

Benefits of technology

CIA biological ink has high solubility under neutral conditions, which can directly dissolve and achieve the solubility of> 45mg/ml, which significantly enhances biological activity and promotes cell migration. This biological ink has excellent solubility, uniformity, injection, and stability. It is suitable for different 3D printing techniques. It can print complex three -dimensional models and significantly accelerate the closure of wounds and tissue regeneration in the healing of diabetic wounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367608A_ABST
    Figure CN119367608A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and relates to novel photosensitive collagen bio-ink for 3D printing as well as a preparation method and application thereof, the novel photosensitive collagen bio-ink comprises the following components: 0.5-4.5% m / v of itaconylated collagen solution, 0.1-1.0% m / v of phenyl-2, 4, 6-trimethylbenzoyl lithium phosphate and 0-0.1% m / v of ultraviolet absorbent; compared with the methylacryloylated collagen, the methylacryloylated collagen has the advantages of higher solubility and bioactivity, higher light transmittance, lower and more uniform pushing force, lower contact angle and more accurate printability; the bio-ink is uniform, stable, high in gelation modulus and suitable for different 3D printing technologies; good cell-loaded printing activity and printing precision are achieved, and proliferation and spreading of cells in the gel can be promoted; the dressing printed by using the novel bio-ink loaded cells has an excellent treatment effect on diabetic wounds, and has good clinical application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials and relates to a novel photosensitive collagen bio-ink for 3D printing, a preparation method and an application thereof. Background Art

[0002] In recent years, the application of collagen as bio-ink in 3D printing has made some progress. 3D bioprinting technology can construct complex three-dimensional structures through layer-by-layer deposition, providing new methods and ideas for tissue engineering. The application of collagen in 3D printing has multiple advantages. First, its natural biocompatibility and biodegradability make it an ideal choice for the preparation of biomedical materials. Since collagen is a natural protein, it is well compatible with human tissues and will not cause immune rejection. Secondly, collagen has good biological activity, can promote cell proliferation, migration, adhesion and differentiation, and help to build complex biological tissue structures. In addition, through appropriate chemical modification and cross-linking, the mechanical properties of collagen can be regulated, and a wide range of mechanical properties from soft to rigid are available, which can meet the needs of different tissue engineering applications.

[0003] However, the solubility of collagen is one of the main challenges that limits its application in 3D printing. Collagen has poor solubility under neutral conditions and usually requires an acidic or alkaline environment to fully dissolve. This not only limits its application in biomedicine, but may also cause potential irritation and damage to cells and tissues. Therefore, improving the solubility of collagen under neutral conditions is an important direction of current research.

[0004] The development of photosensitive collagen has broadened the application of collagen in bioprinting. Photosensitive collagen is cross-linked by a photoinitiator under light of a specific wavelength to form a stable gel structure, which has the advantages of simple operation and fast molding speed. The photosensitive collagen currently used in bio-inks is mainly methacryloyl collagen (CMA), but using it as a raw material for bio-ink still has defects such as insufficient solubility and limited mechanical properties; during the printing process, problems such as structural collapse and nozzle clogging are prone to occur, affecting the printing quality and efficiency. At the same time, some collagen bio-inks have weak mechanical properties after gelation, and it is difficult to provide sufficient structural support, which limits their application in loading cells and tissue repair. Therefore, technicians in this field introduce cross-linking agents into methacryloyl collagen to improve its printing performance, but chemical cross-linking agents may lead to potential toxicity risks.

[0005] It is well known to those skilled in the art that an ideal collagen bio-ink should have a series of excellent properties: (1) it can be dissolved in high concentration under neutral conditions, which is easy to prepare and use; (2) it has good uniformity and stability to ensure that no precipitation or phase separation occurs during the printing process; (3) it has good rheological properties so that it can adapt to different 3D printing technologies and ensure the smooth progress of the printing process; (4) it has good cell compatibility and can support cell survival and functional expression; (5) it should also have adjustable physical and chemical properties to meet the different application requirements of tissue engineering and regenerative medicine.

[0006] In response to the requirements of the above-mentioned collagen bio-ink, the inventors took a different approach and changed the modifier of collagen. The collagen was modified with itaconyl anhydride. The obtained itaconylated collagen has a significantly reduced isoelectric point and contact angle, and introduces more hydrophilic groups, so it has higher solubility, can be directly dissolved under neutral conditions and reach a solubility of >45mg / mL; at the same time, the biological activity of collagen is significantly enhanced, which can further promote cell migration. The prepared bio-ink has excellent solubility, uniformity, injectability and stability, and has high transmittance and gel modulus. In different printing methods such as DLP 3D printing and extrusion 3D printing, the bio-ink shows good printability and can print complex three-dimensional models; it has good cell-carrying biocompatibility, can promote the proliferation and spreading of BMSCs cells in the gel, and after DLP printing with high-density cells, it has micron-level printing accuracy and high cell survival rate, which is suitable for precise printing of various cell types including L929, BMSCs and HUVECs, and has a wide range of clinical application potential. The CIA porous gel prepared by the bio-ink showed significantly better wound closure speed and healing quality than the gel prepared by the common CMA bio-ink during the healing process of diabetic wounds, proving the in vivo biosafety and higher bioactivity of the CIA bio-ink. The dressing prepared by the bio-ink loaded with human fibroblasts (HDFs) was applied to the treatment of diabetic wounds, which could significantly promote wound healing and tissue regeneration, showing excellent therapeutic effects and having good clinical application potential. Summary of the invention

[0007] In view of the above technical problems, the object of the present invention is to provide a new type of photosensitive collagen bio-ink for 3D printing, wherein the bio-ink comprises the following components: 0.5% to 4.5% m / v itaconylated collagen solution, 0.1% to 1.0 m / v phenyl-2,4,6-trimethylbenzoyl lithium phosphate and 0 to 0.1% m / v ultraviolet absorber.

[0008] Preferably, the itaconylated collagen solution is prepared by the following method: after the collagen is fully dissolved with acid, itaconylic anhydride (the mass ratio to collagen is 1.3:1) is added during stirring, 6M NaOH solution is added to maintain the pH at 8-9, and the reaction is carried out for 24-48 hours. After dialysis for 3 days, it is freeze-dried to obtain itaconylated collagen containing a photosensitive group.

[0009] Preferably, the collagen is bovine collagen.

[0010] Preferably, the bovine collagen is type I bovine collagen, and / or type II bovine collagen, and / or type II bovine collagen.

[0011] Preferably, the ultraviolet absorber is one or more of lemon yellow and brilliant blue.

[0012] The second object of the present invention is to provide a method for preparing the bio-ink, comprising the following steps:

[0013] (1) The freeze-dried collagen sponge was dissolved in an acetic acid solution, and the pH was adjusted to neutral after it was fully dissolved. Itaconic anhydride (with a mass ratio of 1.3:1 to collagen) was added during stirring, and a 6M NaOH solution was added to maintain the pH to 8-9. After dialysis for 3 days, it was freeze-dried to obtain itaconic acid-containing collagen with a photosensitive group;

[0014] (2) The itaconylated collagen obtained in step (1) is dissolved in acetic acid solution to a concentration of 0.5% to 4.5% m / v, 0.1% to 1.0% m / v of phenyl-2,4,6-trimethylbenzoyl lithium phosphate and 0 to 0.1% m / v of ultraviolet absorber are added, mixed evenly, and centrifuged to remove bubbles to obtain a novel photosensitive collagen bio-ink.

[0015] The third object of the present invention is to provide one or more applications of the biological ink in the preparation of tissue engineering materials, hemostatic materials, wound dressings, and drug delivery materials.

[0016] Preferably, the tissue engineering material comprises one or more of artificial skin, artificial blood vessels, cartilage and bone repair materials and corneal transplant materials.

[0017] The fourth object of the present invention is to provide a dressing for treating diabetic wounds, wherein the dressing is obtained by adding active ingredients to the biological ink and 3D printing.

[0018] The fifth object of the present invention is to provide use of the dressing in treating diabetic wounds.

[0019] The present invention has the following beneficial effects:

[0020] (1) The present invention first prepares a new type of photosensitive collagen, namely, itaconic anhydride-modified collagen (CIA). Compared with traditional collagen, the photosensitive collagen contains more hydrophilic groups, has significantly lower isoelectric point and contact angle, and thus has higher solubility. It can be directly dissolved under neutral conditions and reach a solubility of >45 mg / mL. At the same time, CIA has significantly enhanced biological activity than collagen and can further promote cell migration.

[0021] (2) The present invention also provides a novel photosensitive collagen bio-ink for 3D printing, wherein the bio-ink comprises the following components: 0.5% to 4.5% m / v itaconylated collagen solution, 0.1-1.0% m / v phenyl-2,4,6-trimethylbenzoyl lithium phosphate and 0-0.1% m / v ultraviolet absorber; the bio-ink has higher light transmittance, lower and more uniform pushing force, lower contact angle, and more precise printability than the common methacrylylated collagen; it has excellent solubility, uniformity, injectability and stability, and has a higher gel modulus; in different printing methods such as DLP 3D printing and extrusion 3D printing, the bio-ink exhibits good printability and is capable of printing complex three-dimensional models.

[0022] (3) The bio-ink has good cell-carrying biocompatibility and can promote the proliferation and spreading of BMSCs cells in the gel. After DLP printing with high-density cells, it has micron-level printing accuracy and high cell survival rate. It is suitable for precise printing of various cell types including L929, BMSCs and HUVECs, and has broad clinical application potential.

[0023] (4) During the diabetic wound healing process, the CIA porous gel prepared by the bio-ink showed significantly better wound closure speed, epithelialization and collagen deposition than the gel prepared by the common CMA bio-ink, which proved the in vivo biosafety and higher bioactivity of the CIA bio-ink, and can effectively promote tissue regeneration of diabetic wounds.

[0024] (5) The dressing prepared by the bio-ink loaded with human fibroblasts (HDFs) is used in the treatment of diabetic wounds, which can significantly promote wound healing, epithelialization and collagen deposition, and achieve nearly 100% tissue regeneration of the wound within 17 days, showing excellent therapeutic effects and good clinical application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Representation of the CIA.

[0026] Note: a) SDS-PAGE of COL and CIA; b) Solubility quantification of COL and CIA; c) Full spectrum of circular dichroism 190-260nm; d) First-order derivative of the thermal curves of COL and CIA.

[0027] Figure 2 Biological activity of CIA.

[0028] Note: a) Pictures of HUVECs cell scratches (0h) and cell migration after 48h in Blank, COL, and CIA groups; b) Quantification of cell migration rates in Blank, COL, and CIA groups; c) Immunofluorescence staining of the cytoskeleton of HDFs treated with Blank, COL, and CIA groups.

[0029] Figure 3 Study on the hydrophilicity and uniformity of CIA and CMA.

[0030] Note: a) Contact angle picture of CMA and CIA; b) Quantification of contact angle of CMA and CIA; c) Comparison of extrusion force of CMA and CIA; d) Comparison of light transmittance of CMA and CIA;

[0031] Figure 4 Study on the rheological and photocuring properties of CIA bio-ink.

[0032] Note: a) Changes in viscosity of 0.5% CIA, 1.5% CIA and 2.5% CIA over time at a constant shear rate; b) Changes in storage modulus and loss modulus of 0.5% CIA, 1.5% CIA and 2.5% CIA bio-inks over time under 405nm light; c) Images of 0.5% CIA, 1.5% CIA and 2.5% CIA bio-inks and images of the gel after curing.

[0033] Figure 5 Comparison of DLP 3D printing performance between CMA and CIA.

[0034] Figure 6 CIA is applied to the research of various printing methods and printing models.

[0035] Note: A. DLP 3D printing, ac are different models or display methods; B. Extrusion 3D printing

[0036] Figure 7 3D imaging of live and dead cell staining of cells in gel at different culture times

[0037] Figure 8 Study on the printing performance of CIA carrying multiple cells.

[0038] Note: ah represents different models or different cells.

[0039] Fig. 9 .Study on diabetic wound healing of CMA, CIA and CIA@HDFs.

[0040] Note: a) Schematic diagram of animal experiment; b) Wound healing appearance diagram; c) Superimposed wound diagram; d) Wound healing rate.

[0041] Fig.10 .Histological staining analysis of diabetic wounds.

[0042] Note: a) HE staining; b) Masson staining. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings of the specification. Obviously, the described embodiments are only a part of the present invention, not the whole of the invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In the following examples, unless otherwise specified, the methods used are all conventional methods;

[0045] In the following examples, unless otherwise specified, the reagents used are conventional reagents and can be purchased from the market.

[0046] In the embodiment of the present invention, yak type I collagen is used as raw material (for the extraction method, see invention patent CN113520900B) for 3D printing collagen bio-ink, but the present invention is not limited to bovine collagen, and collagen obtained by any other means can be used, including type I collagen, type II collagen, type III collagen, etc.

[0047] In the following embodiments, the collagen 3D printing bio-ink is called bio-ink before printing and is called hydrogel after 3D printing.

[0048] Example 1. Preparation and characterization of photosensitive collagen

[0049] Preparation of COL solution: The freeze-dried collagen sponge was dissolved in 0.5 M acetic acid solution. After it was fully dissolved, the pH was adjusted to neutral with saturated NaOH to obtain COL solution as a control before CIA modification.

[0050] Synthesis of CIA: Dissolve the freeze-dried collagen sponge in 0.5M acetic acid solution. After fully dissolved, adjust the pH to neutral with saturated NaOH to obtain a collagen solution. Add itaconic anhydride (1.3:1 mass ratio to collagen) to the stirred collagen solution, and add 6M NaOH solution to maintain the pH in the range of 8-9. The reaction is carried out for 24-48 hours, and then dialyzed with ultrapure water for 3 days, with the solution changed every day. Freeze-dried itaconic anhydride collagen (CIA) is obtained.

[0051] Preparation of CIA solution: Itaconylated collagen (CIA) was directly dissolved in neutral PBS solution for SDS-PAGE and circular dichroism experiments.

[0052] The side chains of collagen contain a large number of free amino groups (-NH2). The amino groups react with itaconic anhydride (IA) to form an amide covalent bond connecting the collagen and IA groups. At the same time, each IA group generates a carboxyl group, thereby introducing new carboxyl groups into the collagen. In addition, the hydroxyl groups in collagen can also react with IA to form itaconic esterified collagen. However, since the amino groups in collagen are strong nucleophilic groups, they have an advantage in the ring-opening reaction with IA, and the reaction products should mainly be itaconic esterified collagen. At the same time, the TNBS test also proves that most of the amino groups are involved in the reaction.

[0053] The results of SDS-PAGE showed that ( Figure 1 a), the α1, α2 and β dimer bands of collagen (COL) before the reaction are clearly visible, among which the α1 and α2 bands are between 100-130kD, and the β dimer band is slightly higher than 180kD. The position of the collagen band after IA modification is significantly higher than the band before modification, among which the α1 and α2 bands are between 130-180kD, and the β dimer band is significantly higher than 180kD, indicating that the molecular weight of collagen increases after IA modification, proving the successful modification of IA on collagen molecules.

[0054] Circular dichroism spectra of 1 mg / mL COL and CIA solutions were measured. The results are as follows: Figure 1 c and 1d. Collagen has a negative peak near 200nm and a positive peak near 222nm, representing the typical triple helix structure of collagen ( Figure 1 c). CIA also showed negative and positive peaks at the same position, indicating that the successful modification of IA did not affect the triple helix structure of collagen. At the same time, the thermal curves of COL and CIA were measured and the first-order derivative curve was obtained by derivation ( Figure 1 d), the results show that the thermal transition temperature of CIA is reduced, but still has a thermal transition temperature of 34° C. These results indicate that CIA has a typical triple helical structure and high thermal stability.

[0055] Example 2: Solubility study of COL and CIA

[0056] 50 mg of freeze-dried COL sponge and CIA sponge were dissolved in aqueous solutions of pH 6, pH 7 and pH 8, respectively, and stirred vigorously at room temperature for 24 hours. The dissolved mixture was centrifuged multiple times at high speed (10000 rpm), and the same volume of collagen and CIA supernatant was taken, freeze-dried and re-weighed. The solubility was calculated as the mass of COL or CIA dissolved per mL volume.

[0057] The results are as follows Figure 1 As shown in b, the solubility of CIA at different pH values ​​is significantly greater than that of collagen. This indicates that CIA has excellent water solubility and can be directly dissolved in weak acid, neutral, and weak alkaline environments, with a solubility of up to 45 mg / mL. In contrast, due to the easy self-assembly of collagen in a neutral environment, its solubility is less than 5 mg / mL. This shows that IA modification has great advantages in improving the solubility of collagen.

[0058] Example 3: Study on the biological activity of COL and CIA

[0059] Preparation of COL solution: The freeze-dried collagen sponge was dissolved in 0.5 M DMEM solution. After it was fully dissolved, the pH was adjusted to neutral with saturated NaOH to obtain COL solution as a control before CIA modification.

[0060] Preparation of CIA: The itaconylated collagen (CIA) prepared in Example 1 was directly dissolved in DMEM solution for cell experiments.

[0061] Human umbilical vein endothelial cells (HUVECs) were used to perform a cell scratch test in a six-well plate. 0.2 mg / mL DMEM-dissolved collagen (COL) and CIA solution were added to the scratched well plate, and the blank group (Blank) was treated with DMEM culture medium as a control. The results are shown in Figure 2 As shown in a, after 48 hours of culture, the cells in the blank group migrated slightly toward the scratch, while the migration area of ​​the cells treated with COL was larger. The migration area of ​​the cells treated with CIA was significantly higher than that of the cells treated with COL. Further quantitative analysis of cell migration rate was performed ( Figure 2 b), CIA-treated cells had the largest migration rate (>85%), which was significantly higher than that of COL and blank groups. This indicates that CIA has a higher ability to promote cell migration than collagen, which may be due to the introduction of negatively charged carboxyl groups in the IA group, which enhances the interaction between cells and the matrix, thereby promoting cell migration.

[0062] Serum-free 0.2 mg / mL COL and CIA solution was added to adherent human fibroblasts (HDFs) and cultured for 24 hours with DMEM medium as control. The medium was removed and the cells were stained for actin and nuclei according to the instructions. The results are shown in Figure 2 As shown in Figure c, the actin of the three groups of cells was stretched and the cells were in an adherent state. Among them, the actin network of cells treated with COL was more than that of cells in the Blank group, and the actin was longer. The actin of cells treated with CIA was more stretched than that of the Blank group, but it tended to aggregate into bundles and arrange in an orderly manner compared to COL. This may be caused by the high negative charge in the CIA culture environment, and this feature may be conducive to cell differentiation. The results of the cell experiment showed that CIA had enhanced biological activity compared to pure collagen.

[0063] Example 4. Preparation and screening of CIA bio-ink

[0064] We prepared 12 bio-ink formulations, as shown in Table 1. The specific preparation steps are as follows:

[0065] Preparation of CIA bio-ink 1-3: The freeze-dried CIA sponge prepared in Example 1 is directly added to neutral PBS and dissolved at low temperature; after sufficient dissolution, NaOH is added to stabilize the pH; LAP and ultraviolet absorber UA are added to the pH-stable neutral CIA solution according to the formula, mixed evenly, and centrifuged to remove bubbles to obtain CIA bio-ink 1-3.

[0066] CIA bio-ink 4-10: The freeze-dried CIA sponge prepared in Example 1 was directly added to the cell culture medium and dissolved at low temperature; after sufficient dissolution, NaOH was added to stabilize the pH; LAP and ultraviolet absorber UA were added to the pH-stable neutral CIA solution according to the formula, mixed evenly, and centrifuged to remove bubbles to obtain CIA bio-ink 4-9.

[0067] Synthesis of CMA: Dissolve the freeze-dried collagen sponge in 0.5M acetic acid solution. After fully dissolved, adjust the pH to neutral with saturated NaOH to obtain a collagen solution. Add methacrylic anhydride (1.3:1 mass ratio to collagen) to the stirred collagen solution, and add 6M NaOH solution to maintain the pH in the range of 8-9. The reaction is carried out for 24-48 hours, and then dialyzed with ultrapure water for 3 days, with the solution changed every day. Freeze-drying to obtain methacrylylated collagen (CMA).

[0068] Preparation of CMA bio-ink 11-12: The freeze-dried CMA sponge was stirred with 0.5M acetic acid for 24-48 hours. After it was fully dissolved, the pH was adjusted to neutral with NaOH solution. LAP and ultraviolet absorber UA were added according to the formula, mixed evenly, and centrifuged to remove bubbles to obtain CMA bio-ink 11-12 as a control for the CIA bio-ink in other embodiments.

[0069] It should be noted that since CIA contains a large number of carboxyl groups, the neutrally dissolved CIA solution will gradually turn acidic, so a blocking agent needs to be added to block the dissolved carboxyl groups. Alkali is the simplest and most common reagent for acid neutralization, usually NaOH, so we prefer NaOH as a carboxyl blocking agent to stabilize the pH of CIA bio-ink. In addition, all reagents that can react with carboxyl groups can be used to block carboxyl groups in this step, such as metal ions coordinating carboxyl groups, polyphenol compounds forming non-covalent interactions with carboxyl groups, and chemical cross-linking agents producing cross-linking reactions with carboxyl groups, all of which can play a role in blocking carboxyl groups and can become carboxyl blocking agents in this step.

[0070] Photosensitive collagen CIA has unsaturated double bonds. Under the action of photoinitiator and ultraviolet light, it can release free radicals to carry out free radical polymerization chain reaction, thereby forming intramolecular crosslinking to form gel. Therefore, bio-inks 1-3 (Table 1) were first prepared and the photoinitiators were screened. Lithium phenyl-2,4,6-trimethylbenzoyl phosphate (LAP), riboflavin, and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylacetone (Irgacure 2959) are all common photoinitiators. The experimental results show that bio-ink 1 containing LAP solidifies into a non-flowable gel in only 20 seconds under 365nm light; while bio-ink 2 using riboflavin as a photoinitiator and bio-ink 3 using Irgacure 2959 as a photoinitiator require several minutes to gel. In addition, the gel strength of bio-inks 2 and 3 after curing is significantly lower than that of the gel formed by bio-ink 1. Due to the long curing time and low mechanical strength, bio-inks 2 and 3 cannot be printed on 3D printers, especially DLP 3D printers. Therefore, LAP should be selected as the photoinitiator.

[0071] We further prepared a series of bio-inks 4-10 containing different concentrations of CIA (see Table 1). Since CIA is extremely water-soluble (>45 mg / mL), the concentration of CIA can be selected according to different printing methods and application requirements. Bio-inks 4-7 have lower concentrations and better fluidity, making them suitable for printing methods that require higher precision and resolution, such as DLP 3D printing. Therefore, in subsequent DLP 3D printing experiments, bio-ink 5 was used, and bio-ink 6 was used in animal experiments. Bio-inks 8-10 have high concentrations of CIA and higher viscosity, making them more suitable for mechanical extrusion systems that require pressure, such as extrusion printing. Therefore, in subsequent extrusion printing experiments, bio-ink 8 was used. Bio-inks 9-10 studied the effects of LAP and UA concentrations, among which bio-ink 9 did not add the light-blocking agent UA because of the small amount of LAP added and the slow crosslinking. To ensure sufficient cross-linking, the LAP concentration was increased to 1.0%, and the UA concentration was also increased to 0.1% to ensure printing accuracy. The system has a high viscosity and is suitable for applications that require high mechanical strength. It can also be used for printing methods such as extrusion printing. In subsequent experiments to study the rheological properties of CIA inks and the mechanical properties of gels, bio-inks were used4,7,8.

[0072] Through screening, the range of formula adjustment was obtained, including CIA concentration (0.5%-4.5%), LAP concentration (0.1%-1.0%) and UV absorber concentration (0-0.1%). Due to the large number of adjustable variables, the flexibility of concentration adjustment is extremely high. It can be adjusted according to specific application requirements. Therefore, in addition to the formulas listed in Table 1, bio-inks not limited to these 10 CIA formulas can be prepared according to different application requirements.

[0073] Table 1 Formulations of different bio-inks

[0074]

[0075] Example 5: Study on the properties of CIA and CMA

[0076] The CIA bio-ink 4 and CMA bio-ink 11 prepared in Example 4 were used to conduct experiments on contact angle, extrusion force and transmittance.

[0077] CIA and CMA were solidified into gels in a mold and the contact angles were characterized. Figure 3 As shown in Figures 3a and 3b, the contact angle of 0.5% CMA is greater than 25°, while the contact angle of CIA at the same concentration is significantly smaller than that of CMA, indicating that CIA has better hydrophilicity than CMA.

[0078] CMA has similar solubility to collagen and is easy to self-assemble under neutral conditions. CMA was used as a control for extrusion force to characterize the uniformity of CIA ink ( Figure 3 c). Under the same test conditions, 0.5% CIA requires less extrusion force than 0.5% CMA, and maintains uniform force within 60 seconds, while CMA requires uneven and significantly variable extrusion force. This is because CMA is unstable under neutral conditions, causing it to self-assemble into insoluble substances, thus requiring a greater extrusion force. In addition, even for high concentrations of 1.5% and 2.5% CIA, the extrusion force required is still very small (less than 3N), and the extrusion force is uniform and does not change significantly. The results show that CIA has better uniformity and excellent injectability than CMA under neutral conditions due to its significantly enhanced water solubility, and is suitable for different 3D printing technologies.

[0079] The transmittance of CIA relative to CMA was further studied. The results showed that the transmittance of CIA was significantly higher than that of CMA in the wavelength range of 400-600nm, reaching 90% at a wavelength of 600nm. This high transmittance indicates that the particles in the CIA solution are more evenly distributed, without obvious particles or aggregates, thereby reducing light scattering and improving transmittance ( Figure 3 d). This further proves that CIA has better solubility and uniformity than CMA under neutral conditions. High transmittance and ink uniformity make CIA more advantageous in bioprinting and medical applications that require high transparency and uniformity.

[0080] Example 6. Rheological analysis and photocuring performance study of CIA bio-ink

[0081] According to the formulations of bio-inks 4, 7, and 8 in Table 1, CIA inks with different concentrations were prepared to study their properties ( Figure 4 ). CIA has good water solubility and can be directly dissolved in DMEM medium with pH 7.4. The results showed that 0.5% and 1.5% CIA inks have good fluidity, while 2.5% CIA ink has poor fluidity due to its high concentration. The three concentrations of ink are uniform solutions, with no insoluble substances visible to the naked eye, such as Figure 4 c. Under the condition of shear rate of 0.01 / s, the viscosity of CIA inks of different concentrations changes little over time, showing good time stability. The viscosity is 2.5%>1.5%>0.5%, which is consistent with the trend that increasing concentration leads to increasing viscosity ( Figure 4 a).

[0082] The photocuring properties of three CIA bio-inks were studied. The results showed that under 405nm blue light irradiation, the storage modulus and loss modulus of CIA inks of different concentrations increased with time, indicating that the ink gradually gelled under blue light irradiation and reached the maximum gelation modulus within 20 seconds and maintained stability ( Figure 4b), demonstrating the efficient photocuring performance of CIA ink. The final gelation modulus of CIA with different concentrations is proportional to the concentration, and all of them form gels with high transparency, complete structure and good support ( Figure 4 c). These results indicate that CIA ink has excellent solubility, uniformity, light transmittance and photocuring properties under neutral conditions, showing strong potential for 3D printing applications.

[0083] Example 7: Study on DLP 3D printing performance of CIA and CMA

[0084] A comparative study on printability was conducted using CIA bio-ink 5 and CMA bio-ink 12 prepared in Example 4.

[0085] As a new type of photosensitive collagen bio-ink, CIA bio-ink exhibits excellent solubility, fluidity and uniformity under neutral conditions, and has a high gel modulus, making it very suitable for DLP 3D printing. A three-dimensional multi-layered plant model was selected as the printing model ( Figure 5 ), the results showed that the succulent model printed with CMA bio-ink had unclear stratification, poor structural integrity and printing accuracy. The succulent gel printed with CIA ink accurately reproduced the details of the CAD model, with multiple layers of petals clearly visible, and the printed gel was crystal clear with good light transmittance. This shows that CIA bio-ink has better printability than CMA bio-ink.

[0086] In addition, the CIA-printed mesh has clear meshes visible to the naked eye and can accurately replicate the CAD model ( Figure 6 Aa). Observed under an optical microscope, the intersections and meshes of the grid showed high resolution, clear and smooth edges, and a flat surface, indicating that CIA bioink has excellent printability in DLP 3D printing.

[0087] We also selected the ear as an organ model for printing and display. The results showed that the printed ear accurately reproduced the details of the ear at different angles and had good structural integrity and support ( Figure 6 Ab). At the same time, when pressure was applied to the printed ear and then released, it was found that the printed gel had high strength and could resist deformation and return to its original shape after the pressure was released ( Figure 6 Ac), showing its potential for application in the field of tissue engineering.

[0088] Example 8: Application of CIA bio-ink in extrusion 3D printing

[0089] CIA has a high solubility and can be used to prepare high-concentration CIA bio-ink for extrusion-based biological 3D printing. We used the bio-ink 8 prepared in Example 4 for extrusion printing, and the results were as follows: Figure 6 As shown in Figure B. A ring with a height of 8 mm and an outer diameter of 1 cm was designed for printing. After printing, the ring structure was complete and the outline was clear, and it was able to pass through metal products with corners, indicating that the printed ring had sufficient support. CIA ink has the potential to print hollow tube structures and can be used to prepare artificial lumen stents. In addition, CIA ink is also used to print pyramid structures. The bottom of the printed pyramid has a clear outline, and the edge of the pyramid is clear when viewed from the side. After secondary curing, the printed pyramid gel is very transparent, and its top tip is clearly visible. CIA bioink also shows excellent printability in extrusion 3D printing applications, and has great potential in 3D printing tissue engineering applications.

[0090] Example 9. Biocompatibility of CIA Bio-ink

[0091] We investigated the biocompatibility of CIA bio-ink 6 for encapsulating cells. Figure 7 As shown. BMSCs cells were encapsulated in CIA bio-ink and cultured for 5 days. The cells were taken out on the 1st, 3rd and 5th days, and the gel encapsulating the cells was stained for live and dead cells, and three-dimensional imaging was performed under a laser confocal microscope. After 1 day of culture, there were almost no dead cells in the gel, and the BMSCs survived and spread, evenly distributed in the three-dimensional matrix. After 3 and 5 days of culture, the cells proliferated significantly in the gel, indicating that CIA bio-ink has good biocompatibility and can promote cell proliferation. CIA bio-ink not only has excellent printing performance, but also shows good biocompatibility and the ability to promote cell proliferation, and has great potential in 3D printing and tissue engineering applications.

[0092] Example 10: Study on the Cell-Carrying Printing Performance of CIA Bio-ink

[0093] We further investigated the cell-carrying printing performance of CIA bio-ink 5 using DLP 3D printing ( Figure 8). The four models printed using CIA ink loaded with fibroblasts achieved micron-level printing accuracy (ad). Live and dead cell staining results showed that the printed gel had almost no dead cells after one day of culture, indicating that the cell survival rate was extremely high. This shows that the cells were almost undamaged during the DLP 3D printing process, demonstrating the significant advantages of CIA bio-ink in high-precision cell printing. In addition, we also tested the printing performance of CIA bio-ink in loading BMSCs and HUVECs cells. The results showed that the printed gel also achieved accurate model printing, and the cell survival rate was still very high. This further proves that CIA bio-ink is not only suitable for fibroblasts in DLP 3D printing, but also for other cell types such as BMSCs and HUVECs, and has good biocompatibility and stability. The cell-loaded printing results show the broad application prospects of CIA bio-ink in the field of 3D bioprinting for tissue engineering and regenerative medicine.

[0094] Example 11: Application of CIA bio-ink and its cell-loaded printed dressing in diabetic wound healing

[0095] To investigate the in vivo biocompatibility and bioactivity of CIA bio-ink 6, we used the SD rat diabetic wound model and compared CIA with the most common photosensitive collagen CMA. After the successful modeling of the diabetic wound, an 8mm full-thickness skin defect model was established on the back of the rat, and CMA porous gel, CIA porous gel, and CIA artificial skin loaded with human fibroblasts (CIA@HDFs) were transplanted into the wound. At the same time, the model group without scaffold treatment was used as the control of diabetic wounds (Control), and the wounds of healthy rats without diabetes were used as the control of acute wounds. The results are shown in Figure 2. Fig. 9 As shown, in the 17-day wound healing tracking, the acute wound was basically closed (>90%), while the diabetic wound became infected midway, which seriously affected the wound closure and was still in the inflammatory stage until the 17th day. Compared with the Control group treated without scaffolds, the wounds in the three groups gradually closed over time, and the wound closure was significantly accelerated during the acute inflammatory period (days 3-6), and gradually entered the proliferation and remodeling stages from days 9 to 17. In particular, the healing process of the CIA and CIA@HDFs groups was significantly faster than that of the CMA group, as shown by faster scab formation and scab shedding in the same period of time and smaller wound area. At the same time, the CIA loaded with HDFs had a faster wound closure speed than the cell-free CIA. Tissue staining analysis further confirmed this result. CIA-treated wounds have better healing quality than CMA-treated wounds, which is reflected in significantly faster tissue regeneration and collagen deposition ( Fig.10 ). CIA bio-ink and its cell-loaded artificial skin exhibited excellent biocompatibility and bioactivity in vivo, significantly accelerating the healing of diabetic wounds.

[0096] In summary, the present invention firstly prepares a novel photosensitive collagen, namely itaconic anhydride-modified collagen (CIA). Compared with traditional collagen, the photosensitive collagen contains more hydrophilic groups, has significantly reduced isoelectric point and contact angle, and thus has higher solubility. It can be directly dissolved under neutral conditions and reach a solubility of >45 mg / mL. At the same time, CIA has significantly enhanced biological activity than collagen and can further promote cell migration. A novel photosensitive collagen bio-ink for 3D printing is also provided. The bio-ink comprises the following components: 0.5% to 4.5% m / v itaconylated collagen solution, 0.1-1.0% m / v phenyl-2,4,6-trimethylbenzoyl lithium phosphate and 0-0.1% m / v ultraviolet absorber; the bio-ink has higher light transmittance, lower and more uniform pushing force, lower contact angle and more precise printability than the common methacrylylated collagen; it has excellent solubility, uniformity, injectability and stability, and has a high gel modulus; in different printing methods such as DLP 3D printing and extrusion 3D printing, the bio-ink shows good printability and can print complex three-dimensional models. The bio-ink has good cell-carrying biocompatibility, can promote the proliferation and spreading of BMSCs cells in the gel, and has micron-level printing accuracy and high cell survival rate after DLP printing with high-density cells, and is suitable for precise printing of various cell types including L929, BMSCs and HUVECs, and has a wide range of clinical application potential. The CIA porous gel prepared by the bio-ink showed significantly better wound closure speed, epithelialization and collagen deposition than the gel prepared by the common CMA bio-ink during the healing process of diabetic wounds, proving the in vivo biosafety and higher bioactivity of the CIA bio-ink, which can effectively promote tissue regeneration of diabetic wounds. The dressing prepared by the bio-ink loaded with human fibroblasts (HDFs) is applied to the treatment of diabetic wounds, which can significantly promote wound healing, epithelialization and collagen deposition, and achieve nearly 100% tissue regeneration of wounds within 17 days, showing excellent therapeutic effects and good clinical application potential.

Claims

1. A novel photosensitive collagen bio-ink for 3D printing, characterized in that: The biological ink comprises the following components: 0.5% to 4.5% m / v itaconylated collagen solution, 0.1% to 1.0% m / v phenyl-2,4,6-trimethylbenzoyl lithium phosphate (LAP) and 0 to 0.1% m / v ultraviolet absorber.

2. The novel photosensitive collagen bio-ink according to claim 1, characterized in that: The itaconylated collagen solution is prepared by the following method: after the collagen is fully dissolved with acid, itaconylic anhydride (the mass ratio to collagen is 1.3:1) is added during stirring, 6M NaOH solution is added to maintain the pH at 8-9, and the reaction is carried out for 24-48 hours. After dialysis for 3 days, it is freeze-dried to obtain itaconylated collagen containing a photosensitive group.

3. The novel photosensitive collagen bio-ink as claimed in claim 2, characterized in that: The collagen is bovine collagen.

4. The bio-ink according to claim 3, characterized in that: The bovine collagen is type I bovine collagen, and / or type II bovine collagen, and / or type II bovine collagen.

5. The novel photosensitive collagen bio-ink according to claim 1, characterized in that: The ultraviolet absorber is one or more of lemon yellow and brilliant blue.

6. The method for preparing the biological ink according to any one of claims 1 to 5, characterized in that: The steps include: (1) The freeze-dried collagen sponge was dissolved in an acetic acid solution, and the pH was adjusted to neutral after it was fully dissolved. Itaconic anhydride (with a mass ratio of 1.3:1 to collagen) was added during stirring, and a 6M NaOH solution was added to maintain the pH to 8-9. After dialysis for 3 days, it was freeze-dried to obtain itaconic acid-containing collagen with a photosensitive group; (2) The itaconylated collagen obtained in step (1) is dissolved in acetic acid solution to a concentration of 0.5% to 4.5% m / v, 0.1% to 1.0% m / v of phenyl-2,4,6-trimethylbenzoyl lithium phosphate and 0 to 0.1% m / v of ultraviolet absorber are added, mixed evenly, and centrifuged to remove bubbles to obtain a novel photosensitive collagen bio-ink.

7. Use of the bio-ink as described in any one of claims 1 to 5 in the preparation of one or more of tissue engineering materials, hemostatic materials, wound dressings, and drug delivery materials.

8. The use according to claim 7, characterized in that The tissue engineering material includes one or more of artificial skin, artificial blood vessels, cartilage and bone repair materials and corneal transplantation materials.

9. A dressing for treating diabetic wounds, characterized in that: The dressing is obtained by adding active ingredients to the biological ink described in any one of claims 1 to 5 and performing 3D printing.

10. Use of the dressing according to claim 9 in treating diabetic wounds.